2022
DOI: 10.1371/journal.pone.0275617
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors of diabetic retinopathy among Chinese adults with type 2 diabetes in a suburb of Shanghai, China

Abstract: Background To investigate the prevalence and risk factors of diabetic retinopathy (DR) in a Chinese population with type 2 diabetes mellitus (T2DM) in a suburb (Qingpu) of Shanghai, China. Methods A population-based cross-sectional study. A total of 7462 residents with T2DM in Qingpu were enrolled according to the resident health archives from January 2020 to December 2020. Blood and urine samples of the subjects were collected. Disc- and macula-centred retinal images were taken to assess DR. SPSS was used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 52 publications
1
8
0
Order By: Relevance
“…The common modifiable and non‐modifiable risk factors for DR and VTDR from studies conducted in China are summarised in Table 2. These studies indicated that classic risk factors including a longer duration of diabetes and poor control of blood glucose are the major risk factors for DR development 3,18–25,35,36,40–42 . Studies have reported a significantly higher risk of VTDR in patients with a DM duration of more than 15 years than in those with a duration of less than 5 years; however, lower odds ratios of disease duration were observed in patients who developed VTDR than in those who developed DR (Table 2).…”
Section: Epidemiologymentioning
confidence: 98%
See 4 more Smart Citations
“…The common modifiable and non‐modifiable risk factors for DR and VTDR from studies conducted in China are summarised in Table 2. These studies indicated that classic risk factors including a longer duration of diabetes and poor control of blood glucose are the major risk factors for DR development 3,18–25,35,36,40–42 . Studies have reported a significantly higher risk of VTDR in patients with a DM duration of more than 15 years than in those with a duration of less than 5 years; however, lower odds ratios of disease duration were observed in patients who developed VTDR than in those who developed DR (Table 2).…”
Section: Epidemiologymentioning
confidence: 98%
“…These studies indicated that classic risk factors including a longer duration of diabetes and poor control of blood glucose are the major risk factors for DR development. 3,[18][19][20][21][22][23][24][25]35,36,[40][41][42] Studies have reported a significantly higher risk of VTDR in patients with a DM duration of more than 15 years than in those with a duration of less than 5 years; however, lower odds ratios of disease duration were observed in patients who developed VTDR than in those who developed DR (Table 2). One plausible explanation might be the less important role of the duration of DM than glycaemic control in forecasting progression from earlier to later stages of DR once retinopathy is already present.…”
Section: Major Risk Factors For Diabetic Retinopathy In Chinamentioning
confidence: 99%
See 3 more Smart Citations